Zn-Al-Mg-based hot-dip plated steel sheet
By adjusting the chemical composition and structure of the hot-dip plating layer of the Zn-Al-Mg-based hot-dip plating steel plate, the ratio and particle size of the [Zn phase] are ensured, and the problem of satin appearance of the surface is solved, achieving an approximate white appearance and excellent resistance. Corrosive.
Patent Information
- Application Number
- CN202380044951.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-10
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-14
AI Technical Summary
The existing Zn-Al-Mg hot-dip plating steel plate has a variety of phases and structures in the hot-dip plating layer, causing the surface to have a satin appearance, making it difficult to achieve the need for an approximately white appearance and surface defects to be conspicuous.
By adjusting the chemical composition of the hot-dip plating layer, the ratio of the area fraction B of the [Zn phase] to the total area fraction A of [Zn phase] and [Tereutectic structure of Al/MgZn2/Zn] is ensured (B/A) The average particle size of [Zn phase] is controlled to be 2.5 to 10 μm to form a white appearance and reduce the presence of the glossy part.
The approximate white appearance of the hot-dip coating surface is achieved, and the surface defects are not easily conspicuous, while maintaining excellent corrosion resistance.
Smart Images

Figure CN119317729A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a Zn-Al-Mg hot-dip plated steel sheet having a nearly white appearance.
[0002] This application claims priority based on Japanese patent application No. 2022-094356 filed on June 10, 2022, and the contents are cited here. Background Art
[0003] Hot-dip galvanized steel sheets are materials used as steel sheets with good corrosion resistance. Hot-dip galvanized steel sheets, which are representative examples of hot-dip galvanized steel sheets, have been widely used in various manufacturing industries such as automobiles, home appliances, and building materials. In addition, in order to further improve the corrosion resistance of hot-dip galvanized steel sheets, highly corrosion-resistant hot-dip galvanized steel sheets containing Al and Mg in the hot-dip galvanized layer have been proposed. For example, in Patent Documents 1 to 3, Zn-Al-Mg hot-dip galvanized steel sheets are proposed.
[0004] However, in the hot-dip coating layer of the Zn-Al-Mg hot-dip plated steel sheet, four phases and structures, namely, [Al phase], [Zn phase], [MgZn2 phase], and [ternary eutectic structure of Al / MgZn2 / Zn], are mainly included. Furthermore, when the hot-dip coating layer contains Si in addition to Zn, Al, and Mg, it also contains [Mg2Si phase] in addition to the above four phases and structures, and mainly contains these five phases and structures. Thus, in the hot-dip coating layer of the Zn-Al-Mg hot-dip plated steel sheet, the hot-dip coating layer surface has a satin appearance due to the mixture of multiple phases and structures.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 10-226865
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 10-306357
[0009] Patent Document 3: Japanese Patent Application Publication No. 2004-68075 Summary of the invention
[0010] Problems to be solved by the invention
[0011] Zn-Al-Mg hot-dip plated steel sheets are widely used in various manufacturing industries such as automobiles, household appliances, and building materials, just like hot-dip galvanized steel sheets. In recent years, users have increased their requirements for the surface appearance of plated steel sheets. For Zn-Al-Mg hot-dip plated steel sheets, there has been a demand for an appearance that is closer to white than completely white. When the appearance is closer to white, there is an advantage that scratches on the surface of the coating are less noticeable.
[0012] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a Zn-Al-Mg hot-dip plated steel sheet having a hot-dip plated layer surface that has a nearly white appearance, less noticeable surface defects, and excellent corrosion resistance compared to conventional steel sheets.
[0013] Means for solving problems
[0014] In order to solve the above-mentioned problems, the present invention adopts the following configuration.
[0015] [1] A Zn-Al-Mg hot-dip plated steel sheet comprising a steel sheet and a hot-dip plated layer formed on a surface of the steel sheet, wherein:
[0016] The hot-dip coating layer contains Al: 5 to 22 mass %, Mg: 1.0 to 10 mass %, and the remainder contains Zn and impurities in terms of average composition.
[0017] When the thickness of the hot-dip coating is set to t and a 5 mm square cross section parallel to the surface is exposed at any position of 3t / 4 position, t / 2 position or t / 4 position from the surface of the hot-dip coating, the ratio (B / A (%)) of the area fraction B of the [Zn phase] of the coating structure in at least one of the cross sections to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is 20% or more.
[0018] [2] A Zn-Al-Mg hot-dip plated steel sheet comprising a steel sheet and a hot-dip plated layer formed on a surface of the steel sheet, wherein:
[0019] The hot-dip coating layer contains Al: 5 to 22 mass %, Mg: 1.0 to 10 mass %, and the remainder contains Zn and impurities in terms of average composition.
[0020] further comprising one or two selected from the following Group A and Group B,
[0021] When the thickness of the hot-dip galvanized layer is set to t and a 5 mm square cross section parallel to the surface is exposed at any one of the positions 3t / 4, t / 2 or t / 4 from the surface of the hot-dip galvanized layer, the ratio (B / A (%)) of the area fraction B of the [Zn phase] of the coating structure to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] in at least one of the cross sections is 20% or more,
[0022] [Group A] Si: 0.0001 to 2 mass%
[0023] [Group B] Any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C: 0.0001 to 2% by mass in total
[0024] [3] The Zn-Al-Mg hot-dip coated steel sheet according to [1] or [2] above, wherein the area fraction of the [Zn phase] in the coating structure in at least one of the cross sections is 10% or more.
[0025] [4] The Zn-Al-Mg hot-dip coated steel sheet according to [1] or [2] above, wherein the average grain size of the [Zn phase] in the coating structure in at least one of the cross sections is 2.5 to 10 μm.
[0026] [5] The Zn-Al-Mg hot-dip coated steel sheet according to [3] above, wherein the average grain size of the [Zn phase] in the coating structure in at least one of the cross sections is 2.5 to 10 μm.
[0027] [6] The Zn—Al—Mg hot-dip coated steel sheet according to [2] above, wherein the hot-dip coating layer has an average composition containing the group A in mass %.
[0028] [7] The Zn—Al—Mg hot-dip plated steel sheet according to [2] above, wherein the hot-dip plated layer has an average composition containing the B group in mass %.
[0029] Effects of the Invention
[0030] According to the present invention, it is possible to provide a Zn-Al-Mg hot-dip plated steel sheet having a nearly white appearance on the surface of the hot-dip plated layer compared to the related art, in which surface defects are less noticeable and which has excellent corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic cross-sectional view for explaining an exposed surface for measuring the coating structure of a hot-dip coated layer in a Zn—Al—Mg-based hot-dip coated steel sheet according to an embodiment of the present invention.
[0032] Figure 2 This is a perspective view for explaining an exposed surface used for measuring the coating structure of a hot-dip coated layer in a Zn—Al—Mg-based hot-dip coated steel sheet according to an embodiment of the present invention. DETAILED DESCRIPTION
[0033] The inventors of the present invention have conducted detailed studies on the coating of conventional Zn-Al-Mg hot-dip plated steel sheets showing a satin appearance. The satin appearance is exhibited by the presence of a fine glossy portion showing a metallic luster and a fine white portion showing a white color mixed together. Among them, the structure of the hot-dip coating in the white portion was studied, and it was found that the ratio of [Zn phase] to the sum of [Zn phase] and [ternary eutectic structure of Al / MgZn2 / Zn] was higher than that in the glossy portion. In addition, it was found that the ratio of [Zn phase] in the hot-dip coating was also relatively high.
[0034] Therefore, the present inventors have conducted intensive research to obtain a white appearance as a whole by reducing the glossy part while having a large amount of white parts in the hot-dip coating layer, and have found that the surface appearance of the hot-dip coating layer can be made white as a whole by adjusting the chemical composition of the hot-dip coating layer and increasing the ratio of the [Zn phase]. In particular, it has been found that it is effective to increase the ratio of the [Zn phase] to the total of the [ternary eutectic structure of Al / MgZn2 / Zn] and the [Zn phase] in the hot-dip coating layer as a whole.
[0035] Hereinafter, a Zn—Al—Mg-based hot-dip plated steel sheet according to an embodiment of the present invention will be described.
[0036] The Zn-Al-Mg hot-dip plated steel sheet of the present embodiment comprises a steel sheet and a hot-dip plated layer formed on the surface of the steel sheet, wherein the hot-dip plated layer contains Al: 5 to 22 mass %, Mg: 1.0 to 10 mass % in average composition, and the remainder contains Zn and impurities, and when a 5 mm square cross section parallel to the hot-dip plated layer surface is exposed at any one of the positions 3t / 4, t / 2 or t / 4 from the hot-dip plated layer surface, the ratio (B / A (%)) of the area fraction B of the [Zn phase] of the plated structure in at least one of the cross sections to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is 20% or more. Here, the so-called "5 mm square cross section parallel to the hot-dip plated layer surface" refers to a square exposed surface parallel to the hot-dip plated layer surface and having a width of 5 mm square in a plan view.
[0037] The material of the steel material that serves as the base of the hot-dip coating is not particularly limited. As the material, ordinary steel, aluminum-killed steel, and some high-alloy steels can be used, and the shape is not particularly limited. In addition, the steel material may be pre-plated with Ni. The hot-dip coating layer involved in this embodiment can be formed by applying the hot-dip coating method described later to the steel material.
[0038] Next, the chemical composition of the hot-dip coating will be described.
[0039] The hot-dip coating layer according to the present embodiment contains, in average composition, 5 to 22% by mass of Al and 1.0 to 10% by mass of Mg, and the remainder contains Zn and impurities.
[0040] One or two selected from the following Group A and Group B may be further contained.
[0041] [Group A] Si: 0.0001 to 2 mass%
[0042] [Group B] Any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C: 0.0001 to 2% by mass in total
[0043] The Al content is in the range of 5 to 22 mass % based on the average composition. Al is an element necessary to ensure corrosion resistance. If the Al content in the hot-dip coating is less than 5 mass %, the effect of improving corrosion resistance is not sufficient. If the Al content in the hot-dip coating exceeds 22 mass %, the corrosion resistance sometimes decreases, although the reason is unknown. From the viewpoint of corrosion resistance, the lower limit of the Al content in the hot-dip coating is preferably 6 mass % or more, more preferably 11 mass % or more. The upper limit of the Al content in the hot-dip coating is preferably 20 mass % or less, more preferably 19 mass % or less.
[0044] The Mg content is in the range of 1.0 to 10% by mass based on the average composition. Mg is an element necessary to improve the corrosion resistance of the hot-dip coating. If the Mg content in the hot-dip coating is less than 1.0% by mass, the effect of improving the corrosion resistance is not sufficient. If the Mg content in the hot-dip coating exceeds 10% by mass, the generation of dross in the plating bath becomes significant, and it becomes difficult to stably manufacture the plated steel. From the viewpoint of the balance between corrosion resistance and dross generation, the lower limit of the Mg content in the hot-dip coating is preferably 1.5% by mass or more, and more preferably 2% by mass or more. The upper limit of the Mg content in the hot-dip coating is preferably 8% by mass or less, and more preferably in the range of 6% by mass or less.
[0045] In addition, the hot-dip coating may also contain Si in the range of 0.0001 to 2 mass%. Si is an effective element for improving the adhesion of the hot-dip coating. Since the effect of improving adhesion is shown by containing more than 0.0001 mass% of Si, it is preferred to contain more than 0.0001 mass% of Si. On the other hand, if the Si content in the hot-dip coating exceeds 2 mass%, the effect of improving the adhesion of the coating is saturated, so the Si content is set to less than 2 mass%. From the viewpoint of coating adhesion, the lower limit of the Si content in the hot-dip coating is more preferably more than 0.01 mass%, and more preferably more than 0.03%. The upper limit of the Si content in the hot-dip coating is more preferably less than 1 mass%, and more preferably less than 0.8 mass%.
[0046] In addition, in the hot-dip coating, any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C may be contained in total in an average composition of 0.0001 to 2 mass %. Preferably, it is 0.001 mass % or more, or 0.01 mass % or more. In addition, it is 2 mass % or less. By containing any one or more of these elements, the corrosion resistance can be further improved. "REM" is one or more of the rare earth elements with atomic numbers of 57 to 71 in the periodic table.
[0047] The remainder of the chemical composition of the hot-dip coating is zinc and impurities.
[0048] Furthermore, the composition of the hot-dip coating can be measured by the following method. First, after removing the surface coating with a coating stripper that does not corrode the coating (e.g., NEOREVER SP-751 manufactured by Sancai Chemical Co., Ltd.), the hot-dip coating is dissolved with hydrochloric acid to which a corrosion inhibitor (e.g., HIBIRON manufactured by Sugimura Chemical Industry Co., Ltd.) is added, and the composition of the hot-dip coating is determined by performing inductively coupled plasma (ICP) emission spectroscopy analysis on the obtained solution.
[0049] Next, the structure of the hot-dip coating layer will be described. The structure of the hot-dip coating layer of the present embodiment may have the following structure, for example.
[0050] The hot-dip galvanized layer containing Al, Mg and Zn includes [Al phase], [MgZn2 phase], [Zn phase] and [ternary eutectic structure of Al / Zn / MgZn2]. Specifically, in the matrix of [ternary eutectic structure of Al / Zn / MgZn2], there is a morphology including [Al phase], [MgZn2 phase] and [Zn phase]. In addition, when Si is contained, [Mg2Si phase] may also be included in the matrix of [ternary eutectic structure of Al / Zn / MgZn2].
[0051] [Ternary eutectic structure of Al / Zn / MgZn2]
[0052] The so-called [ternary eutectic structure of Al / Zn / MgZn2] is a ternary eutectic structure of Al phase, Zn phase and intermetallic compound MgZn2 phase. The Al phase forming the ternary eutectic structure is equivalent to, for example, the "Al" phase at high temperature in the ternary equilibrium phase diagram of Al-Zn-Mg (which is an Al solid solution of solid dissolved Zn and contains a small amount of Mg).
[0053] The Al" phase at high temperature is usually separated into a fine Al phase and a fine Zn phase at room temperature. The Zn phase in the ternary eutectic structure is a Zn solid solution in which a small amount of Al and, depending on the situation, a small amount of Mg is further dissolved. The MgZn2 phase in the ternary eutectic structure is an intermetallic compound phase existing near Zn: about 84 mass% in the Zn-Mg binary system equilibrium phase diagram.
[0054] From the phase diagram alone, it can be considered that no other added elements are dissolved in each phase, or even if dissolved, they are extremely small. However, their amounts cannot be clearly distinguished in ordinary analysis, so in this specification, the ternary eutectic structure composed of these three phases is expressed as [ternary eutectic structure of Al / Zn / MgZn2].
[0055] [Al phase]
[0056] The so-called [Al phase] is a phase with clear boundaries and can be seen as an island in the matrix of the [ternary eutectic structure of Al / Zn / MgZn2]. This is equivalent to the "Al" phase at high temperature in the ternary equilibrium phase diagram of Al-Zn-Mg (which is an Al solid solution containing Zn and a small amount of Mg). The Al" phase at high temperature has different amounts of dissolved Zn or Mg depending on the concentration of Al or Mg in the plating bath. It can be considered that the Al" phase at high temperature is usually separated into fine Al phase and fine Zn phase at room temperature, but the island shape seen at room temperature is caused by the shape of the Al" phase at high temperature.
[0057] Judging from the phase diagram alone, it can be considered that no other added elements are dissolved in this phase, or even if dissolved, they are only in very small amounts. However, since it is not possible to clearly distinguish them in ordinary analysis, the phase derived from the Al" phase at high temperature and whose shape is derived from the shape of the Al" phase is referred to as "Al phase" in this specification.
[0058] The [Al phase] can be clearly distinguished from the Al phase forming the [ternary eutectic structure of Al / Zn / MgZn2] in microscopic observation.
[0059] [Zn phase]
[0060] The so-called [Zn phase] is a phase that has a clear boundary and can be seen as an island in the matrix of the [ternary eutectic structure of Al / Zn / MgZn2]. In fact, a small amount of Al and a small amount of Mg are sometimes dissolved. From the phase diagram alone, it can be considered that no other added elements are dissolved in this phase, or even if they are dissolved, they are extremely small.
[0061] The Zn phase is a region with an equivalent circle diameter of 2.5 μm or more, and can be clearly distinguished from the Zn phase forming the ternary eutectic structure of Al / Zn / MgZn2 under microscope observation. The Zn phase may also have an equivalent circle diameter of 10 μm or less.
[0062] [MgZn2 phase]
[0063] The so-called [MgZn2 phase] is a phase that has a clear boundary and can be seen as an island in the matrix of the [ternary eutectic structure of Al / Zn / MgZn2], and in fact, a small amount of Al is sometimes dissolved. Judging from the phase diagram alone, it can be considered that no other added elements are dissolved in this phase, or even if they are dissolved, they are extremely small.
[0064] The [MgZn2 phase] and the MgZn2 phase forming the [ternary eutectic structure of Al / Zn / MgZn2] can be clearly distinguished in microscopic observation. In the hot-dip coating of the present embodiment, the [MgZn2 phase] may not be contained due to different manufacturing conditions, but the [MgZn2 phase] may be contained in the hot-dip coating under most manufacturing conditions.
[0065] [Mg2Si phase]
[0066] The so-called [Mg2Si phase] is a phase that has a clear boundary and can be seen as an island in the solidified structure of the hot-dip coating to which Si is added. From the phase diagram alone, it can be considered that Zn, Al, and other added elements are not dissolved in the [Mg2Si phase], or even if they are dissolved, they are extremely small. The [Mg2Si phase] can be clearly distinguished from other phases in the hot-dip coating when observed under a microscope.
[0067] Next, the content of [Zn phase] is described. In this embodiment, Figure 1 and Figure 2As shown, when the thickness of the hot-dip coating 2 formed on the steel sheet 1 is t, and a cut is made at any position of 3t / 4 position, t / 2 position or t / 4 position from the surface 2a of the hot-dip coating 2 so that a square-shaped exposed surface 3, 4, 5 parallel to the surface 2a and having a width of 5 mm square in a plan view appears, in at least one of these exposed surfaces 3 to 5, the ratio (B / A (%)) of the area fraction B of the [Zn phase] of the coating structure to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is 20% or more. The ratio (B / A (%)) may be 25% or more, or 30% or more. By making the ratio of [Zn phase] to the total of [Zn phase] and [ternary eutectic structure of Al / MgZn2 / Zn] 20% or more, the proportion of fine white parts showing white on the surface of the hot-dip galvanized layer increases, and the overall appearance of the hot-dip galvanized layer can appear white. The upper limit of the ratio (B / A (%)) does not need to be particularly limited, but it can also be 70% or less, 60% or less, or 55% or less. Furthermore, Figure 1 The cross-sectional diagram shown is along Figure 2 Cross-sectional view of the AA′ plane.
[0068] In addition, in at least one of the exposed surfaces 3 to 5, the area fraction of the [Zn phase] of the coating structure is preferably 20% or more. The area fraction of the [Zn phase] may be 25% or more, or 30% or more. By making the area fraction of the [Zn phase] 20% or more, the proportion of the fine white portion showing white in the surface of the hot-dip coating increases, and the overall appearance of the hot-dip coating can be more white. The upper limit of the area fraction of the [Zn phase] does not need to be particularly limited, but it may be 60% or less, 50% or less, or 40% or less.
[0069] In at least one of the exposed surfaces 3 to 5, the average grain size of the [Zn phase] in the plating structure is preferably 2.5 to 10 μm. By setting the average grain size of the [Zn phase] to 2.5 to 10 μm, the surface appearance can be made closer to white.
[0070] Furthermore, the area fraction of the [Al phase] in the exposed surface where the area fraction of the [Zn phase] is measured may be, for example, 10 to 80 area % or 20 to 65 area %.
[0071] In addition, the area fraction of the [ternary eutectic structure of Al / MgZn2 / Zn] in the exposed surface where the area fraction of the [Zn phase] is measured may be, for example, 10 to 80 area % or 20 to 65 area %.
[0072] Furthermore, the area fraction of the [MgZn2 phase] in the exposed surface where the area fraction of the [Zn phase] is measured may be, for example, 0 to 60 area % or 10 to 40 area %.
[0073] Furthermore, the area fraction of the [Mg 2 Si phase] in the exposed surface where the area fraction of the [Zn phase] is measured may be, for example, 0 to 5 area % or 0 to 1 area %.
[0074] When the exposed surface 3, 4, 5 of 5 mm square parallel to the surface is exposed at any position of the 3t / 4 position, t / 2 position or t / 4 position from the surface 2a of the hot-dip coating 2, the hot-dip coating is removed by means such as grinding and argon sputtering. In addition, it is preferred to make the exposed surface a mirror surface, for example, it is preferred to set the maximum height Rz of the profile of the exposed surface to be less than 0.2 μm. The exposed surface as the object of observation may also be an exposed surface at any depth of the 3t / 4 position, t / 2 position or t / 4 position from the surface of the hot-dip coating. The exposed surface at the t / 2 position is preferably selected. In the exposed surface at the t / 2 position, as long as the B / A ratio or the area fraction of the [Zn phase] meets the scope of the present invention, the possibility of the B / A ratio or the area fraction of the [Zn phase] at other positions meeting the scope of the present invention is high. More preferably, in the exposed surface at any two depths of 3t / 4 position, t / 2 position or t / 4 position from the hot-dip coating surface, the B / A ratio of [Zn phase] or the area fraction of [Zn phase] can satisfy the scope of the present invention. Further preferably, in the exposed surface at all depths of 3t / 4 position, t / 2 position or t / 4 position from the hot-dip coating surface, the B / A ratio of [Zn phase] or the area fraction of [Zn phase] can satisfy the scope of the present invention.
[0075] For the exposed surface with a size of 5mm×5mm, the coating structure was observed by using the secondary electron image of a scanning electron microscope (SEM) to identify the [Zn phase] and [ternary eutectic structure of Al / MgZn2 / Zn]. When identifying each phase and structure, elemental analysis based on the energy dispersive X-ray elemental analysis device attached to the SEM was used to confirm the distribution of Zn, Al and Mg. That is, among Zn, Al and Mg, the area where Zn was mainly detected was the Zn phase, the area where Al was mainly detected was the Al phase, and the area where Zn and Mg were mainly detected was the MgZn2 phase. From the distribution of each detected phase, according to the above method, it was classified into [Al phase], [MgZn2 phase] and [Zn phase], and [ternary eutectic structure of Al / Zn / MgZn2]. Then, the area fraction of [Zn phase] in the exposed surface is calculated, and also the ratio of the area fraction B of [Zn phase] to the total area fraction A of [Zn phase] and [ternary eutectic structure of Al / MgZn2 / Zn] (B / A(%)) is calculated.
[0076] In addition, the average grain size of the [Zn phase] of the coating structure is measured on the exposed surfaces 3 to 5. The average grain size is set as the average equivalent circle diameter. While measuring the number of [Zn phases] on each exposed surface 3 to 5, the total area of [Zn phases] on each exposed surface 3 to 5 is calculated. Next, the area of each [Zn phase] is calculated by dividing the total area of [Zn phases] by the number, and the average equivalent circle diameter is calculated from the area.
[0077] Next, a method for producing the Zn—Al—Mg based hot dip coated steel sheet according to the present embodiment will be described.
[0078] When manufacturing the Zn-Al-Mg hot-dip coated steel sheet of the present embodiment, it is necessary to control the structure of the hot-dip coated layer in order to reduce the area fraction of the [Zn phase] in the exposed surface parallel to the surface at any one of the positions 3t / 4, t / 2 or t / 4 from the surface of the hot-dip coated layer.
[0079] To manufacture Zn-Al-Mg hot-dip plated steel sheets by hot-dip plating, the steel sheet is immersed in a hot-dip plating bath with adjusted chemical composition to allow the molten metal to adhere to the surface of the steel sheet. Next, the steel sheet is lifted from the plating bath, and after the amount of adhesion is controlled by gas friction contact, the molten metal is solidified. During solidification, although it also depends on the composition, [Al phase] is formed first, and then [ternary eutectic structure of Al / Zn / MgZn2] is formed as the temperature of the molten metal drops. In addition, [MgZn2 phase] and [Zn phase] are formed in the matrix of [ternary eutectic structure of Al / Zn / MgZn2]. In addition, when Si is contained in the hot-dip plating layer, [Mg2Si phase] is formed in the matrix of [ternary eutectic structure of Al / Zn / MgZn2].
[0080] When a coarse [Zn phase] is formed, the ratio of [Al phase] and [MgZn2 phase] in the hot-dip coating increases relatively, and it is known that the appearance of the hot-dip coating surface is nearly white because these phases are exposed to the coating surface. It can be inferred that the formation of the [Zn phase] is affected by the number of Zn nucleation points. In other words, the inventors have obtained the following insights: when there are few Zn nucleation points, the Zn in the liquid phase just before the final solidification does not crystallize and precipitate as a fine Zn phase in the [ternary eutectic structure of Al / Zn / MgZn2], but crystallizes and precipitates as a coarse [Zn] phase. As a means of reducing the Zn nucleation points, it is possible to consider improving the surface cleanliness of the original plate, i.e., the steel plate, and reducing the substances that can become Zn nucleation points as much as possible.
[0081] The details of the production method will be described below.
[0082] The hot rolled steel sheet is manufactured and annealed as required. After pickling, cold rolling is performed as required to form a cold rolled sheet. The hot rolled sheet or cold rolled sheet is degreased and washed with water, and then annealed. The annealed hot rolled sheet or cold rolled sheet is immersed in a hot dip coating bath to form a hot dip coating.
[0083] Before annealing, the steel sheet is subjected to alkaline electrolytic cleaning to improve surface purity, washed with pure water, and then dried in an inert atmosphere to remove moisture from the surface of the steel sheet, and then the process proceeds to the annealing step.
[0084] As a cleaning solution used in alkaline electrolytic cleaning, an alkaline cleaning solution containing sodium hydroxide or potassium hydroxide is preferred. As a step of alkaline electrolytic cleaning, the steel plate is immersed in the cleaning solution for immersion cleaning, and then the steel plate is electrolytically cleaned in the cleaning solution. The electrolytic cleaning is preferably alternating electrolytic cleaning. Then, the attached cleaning solution is rinsed off by spraying pure water onto the surface of the steel plate. Regarding the water jet washing, a plurality of spray nozzles may be arranged along the forward direction of the steel plate, and pure water may be sprayed from each nozzle. As pure water, water having a resistivity of 1 MΩ·cm or more is preferably used.
[0085] Annealing after alkaline electrolytic cleaning is preferably performed within 10 seconds from the end of alkaline electrolytic cleaning. The end of alkaline electrolytic cleaning is preferably set to the extraction of the last pure water jet washing of alkaline electrolytic cleaning. Annealing conditions are not particularly limited.
[0086] In addition, during the period from the extraction of the spray water washing to the annealing, drying in an inert atmosphere is performed to remove as much moisture as possible attached to the surface of the steel sheet. This method is preferred in that it can suppress the attachment of fine suspended particles in the air. Drying can be performed by dispersing the moisture by spraying an inert gas and then evaporating it.
[0087] By removing organic dirt attached to the surface of the steel sheet by alkaline electrolytic cleaning, and then annealing within 10 seconds after the final pure water jet washing, it is possible to prevent fine suspended particles in the air from adhering to the cold-rolled sheet. If the annealing start time exceeds 10 seconds from the final jet washing, the surface purity of the steel sheet may decrease.
[0088] Next, the steel sheet is immersed in a hot dip coating bath. Preferably, the hot dip coating bath contains 5 to 22 mass % of Al, 1.0 to 10 mass % of Mg, and the remainder contains Zn and impurities. In addition, the hot dip coating bath may contain 0.0001 to 2 mass % of Si. In addition, the hot dip coating bath may contain 0.0001 to 2 mass % of any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C in total.
[0089] The temperature of the hot-dip coating bath is preferably in the range of 400 to 500° C. When the temperature of the hot-dip coating bath is in this range, a desired hot-dip coating layer can be formed.
[0090] The amount of hot-dip coating can be adjusted by means of friction contact of the steel sheet lifted from the hot-dip coating bath with gas. The amount of hot-dip coating is preferably adjusted to a total of 30 to 600 g / m2 on both sides of the steel sheet. 2 When the adhesion is less than 30g / m 2 When the adhesion amount exceeds 600g / m 2 When hot-dip galvanizing is performed, the molten metal adhering to the steel sheet drips and the hot-dip galvanized surface cannot be smoothly formed, which is not preferred.
[0091] After adjusting the amount of hot-dip coating, the steel sheet is cooled. The cooling of the molten metal attached to the steel sheet begins after the steel sheet is lifted from the hot-dip coating bath. Although it also depends on the composition of the hot-dip coating bath, for example, [Al phase] begins to crystallize from around 430°C. Then, [MgZn2] begins to crystallize from around 370°C, [ternary eutectic structure of Al / Zn / MgZn2] crystallizes from around 340°C, and then [Zn phase] crystallizes, thereby completing solidification.
[0092] At this time, due to the reduction of Zn nucleation sites on the steel plate surface, it becomes difficult for Zn or MgZn2 as the eutectic structure to crystallize, which reduces the [ternary eutectic structure of Al / Zn / MgZn2]. On the other hand, the Zn in the liquid phase increases, thereby forming more [Zn phase].
[0093] When a chemical conversion treatment layer is formed on the surface of the hot-dip coating layer, the hot-dip coated steel sheet after the hot-dip coating layer is subjected to a chemical conversion treatment. The type of chemical conversion treatment is not particularly limited, and a known chemical conversion treatment can be used.
[0094] When a coating layer is formed on the surface of the hot-dip coating layer and the surface of the chemical conversion treatment layer, the hot-dip coated steel sheet is subjected to a coating treatment after the hot-dip coating layer or the chemical conversion treatment layer is formed. The type of coating treatment is not particularly limited, and a known coating treatment can be used.
[0095] As described above, according to the present embodiment, the metallic glossiness of the hot-dip coating surface can be improved compared with the related art.
[0096] Example
[0097] Next, examples of the present invention will be described. After cold-rolled steel sheets were cleaned by alkaline electrolysis, cold-rolled sheets were annealed after the elapse of the time shown in Table 1A and Table 1B.
[0098] As a cleaning solution used in alkaline electrolytic cleaning, an alkaline cleaning solution containing sodium hydroxide is specified. As a step of alkaline electrolytic cleaning, after immersing the steel plate in the cleaning solution for immersion cleaning, the steel plate is electrolytically cleaned in the cleaning solution. Electrolytic cleaning is specified as alternating electrolytic cleaning. Then, the attached cleaning solution is rinsed by pure water jet washing. As pure water, water with a resistivity of 1MΩ·cm or more is specified. Then, while drying in an inactive atmosphere, the cold-rolled sheet is annealed after the time shown in Table 1A and Table 1B has passed since the final jet washing. The annealing conditions are specified as a soaking temperature of 800°C and a soaking time of 1 minute.
[0099] Next, the cold-rolled steel sheet after annealing was immersed in a hot-dip coating bath and then pulled out. Then, the adhesion amount was adjusted by gas friction contact, and then cooled. Furthermore, in No. 66, ultrapure water jet washing and drying were performed without alkaline electrolytic cleaning, and in No. 67, annealing was started 15 seconds after jet washing. In this way, the hot-dip coated steel sheets of No. 1 to 67 shown in Table 1A to Table 2B were manufactured.
[0100] For the obtained hot-dip galvanized steel sheet, Figure 1 and Figure 2 As shown, exposed surfaces of 5 mm square parallel to the surface are formed at positions t / 4, t / 2 and 3t / 4 from the hot-dip coating surface. The exposed surfaces are formed by removing the hot-dip coating by grinding and then mirror-polishing.
[0101] For the exposed surface with a size of 5mm×5mm, the coating structure is observed by secondary electron imaging of a scanning electron microscope (SEM) to identify the [Zn phase] and [ternary eutectic structure of Al / MgZn2 / Zn]. When identifying each phase and structure, elemental analysis based on an energy dispersive X-ray elemental analyzer attached to the SEM is used to confirm the distribution of Zn, Al and Mg. Then, the area fraction of the [Zn phase] in each exposed surface is calculated, and then the ratio of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is calculated (B / A(%)). Regarding the [Zn phase], the structure of the area with an equivalent circle diameter of 2.5μm or more is measured as the [Zn phase]. In this way, the Zn phase and the [Zn phase] in the [ternary eutectic structure of Al / MgZn2 / Zn] are distinguished.
[0102] The results are shown in Table 2A and Table 2B.
[0103] In addition, in the exposed surfaces of No. 1 to 61 where the area fraction of the [Zn phase] was measured, the area fraction of the [Al phase] was in the range of 30 to 80 area %. In addition, in the same exposed surface, the area fraction of the [ternary eutectic structure of Al / MgZn2 / Zn] was in the range of 10 to 75 area %. In addition, in the same exposed surface, the area fraction of the [MgZn2 phase] was in the range of 0 to 60 area %. In addition, in the same exposed surface, the area fraction of the [Mg2Si phase] was in the range of 0 to 5 area %.
[0104] Furthermore, the hot-dip coating surface of the obtained hot-dip coated steel sheet was observed and visually evaluated based on the following criteria. A and B were defined as acceptable. The results are shown in Table 2A and Table 2B.
[0105] A: No scratches were observed even from 0.5 m ahead.
[0106] B: Operation scratches were observed from 0.5 m forward, but no operation scratches were observed from 2 m forward.
[0107] C: Handling scratches were also observed from 2 m ahead.
[0108] The corrosion resistance of hot-dip galvanized steel sheets was evaluated by the corrosion loss after the CCT test. The plated steel sheets were cut into 150×70 mm pieces and the corrosion loss after 30 CCT cycles was investigated using the CCT test based on JASO-M609. The corrosion loss was evaluated to be less than 30 g / m 2 Set F to 30 g / m 2 Above and below 50g / m 2 Set G to 50 g / m 2 The above is defined as P, and F and G are defined as pass.
[0109] Table 1A
[0110]
[0111] Table 1B
[0112]
[0113] The underlined characters indicate conditions outside the scope of the present invention or outside the range of preferred production conditions.
[0114] Table 2A
[0115]
[0116] Table 2
[0117]
[0118] The dashed lines indicate that the hot-dip plated steel sheets No. 1 to No. 61 are outside the scope of the present invention. Since the chemical composition of the hot-dip coating is within the scope of the present invention, the hot-dip coating is performed after alkaline electrolytic cleaning, pure water jet washing, drying and annealing, so the nucleation points of Zn in the steel sheet surface are reduced, and when a 5 mm square exposed surface is formed at the 3t / 4 position, t / 2 position or t / 4 position from the hot-dip coating surface, the ratio of the coating structure (B / A (%)) in at least one exposed surface becomes 20% or more. Therefore, the appearance of the hot-dip coating becomes a white appearance, and scratches become less noticeable. In addition, the corrosion resistance is also good. In addition, in No. 1 to No. 61, in each exposed surface at the 3t / 4 position, t / 2 position and t / 4 position, the average particle size of the [Zn phase] is in the range of 2.5 to 10 μm.
[0119] The hot-dip plated steel sheet No. 62 has a low Al content in the hot-dip plated layer, and the ratio (B / A (%)) in each exposed surface at the 3t / 4 position, t / 2 position, and t / 4 position is less than 20%, and scratches become easily conspicuous. In addition, the corrosion resistance is reduced due to the low Al content in the hot-dip plated layer.
[0120] The hot-dip plated steel sheet No. 63 had excessive Al content in the hot-dip plated layer, so the corrosion resistance was reduced.
[0121] The hot-dip plated steel sheet No. 64 has a low Mg content in the hot-dip plated layer, and the ratio (B / A (%)) in each exposed surface at the 3t / 4 position, t / 2 position, and t / 4 position is less than 20%, and scratches become easily conspicuous. In addition, the corrosion resistance is reduced due to the low Mg content in the hot-dip plated layer.
[0122] The hot-dip plated steel sheet No. 65 had an excessive Mg content in the hot-dip plated layer, so the corrosion resistance was reduced.
[0123] Since the hot-dip galvanized steel sheet No. 66 was not subjected to alkaline electrolytic cleaning and only subjected to pure water jet washing and drying, the synergistic effect of alkaline electrolytic cleaning and jet water washing was not obtained, the nucleation point of Zn increased, and the ratio (B / A (%)) at the position 3t / 4, t / 2 or t / 4 from the surface of the hot-dip galvanized layer became less than 20%, and scratches became easily conspicuous.
[0124] Since the hot-dip plated steel sheet No. 67 was annealed 15 seconds after the water jet washing, the nucleation point of Zn increased, and the ratio (B / A (%)) became less than 20% at the 3t / 4 position, t / 2 position or t / 4 position from the hot-dip plated layer surface, and scratches became conspicuous.
[0125] Industrial Applicability
[0126] The Zn—Al—Mg hot-dip plated steel sheet disclosed herein has high industrial applicability because the hot-dip plated layer surface has a nearly white appearance, surface defects are less noticeable, and corrosion resistance is excellent.
[0127] Explanation of symbols
[0128] 1: steel plate, 2: hot-dip coating, 2a: hot-dip coating surface, 3: cross section at t / 4 position (exposed surface), 4: cross section at t / 2 position (exposed surface), 5: cross section at 3t / 4 position (exposed surface).
Claims
1. A Zn-Al-Mg hot-dip plated steel sheet comprising a steel sheet and a hot-dip plated layer formed on a surface of the steel sheet, wherein: The hot-dip coating layer contains Al: 5 to 22 mass %, Mg: 1.0 to 10 mass %, and the remainder contains Zn and impurities in terms of average composition. When the thickness of the hot-dip coating is set to t and a 5 mm square cross section parallel to the surface is exposed at any position of 3t / 4 position, t / 2 position or t / 4 position from the surface of the hot-dip coating, the ratio (B / A (%)) of the area fraction B of the [Zn phase] of the coating structure in at least one of the cross sections to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is 20% or more.
2. A Zn-Al-Mg hot-dip plated steel sheet comprising a steel sheet and a hot-dip plated layer formed on a surface of the steel sheet, wherein: The hot-dip coating layer contains Al: 5 to 22 mass %, Mg: 1.0 to 10 mass %, and the remainder contains Zn and impurities in terms of average composition. further comprising one or two selected from the following Group A and Group B, When the thickness of the hot-dip galvanized layer is set to t and a 5 mm square cross section parallel to the surface is exposed at any one of the positions 3t / 4, t / 2 or t / 4 from the surface of the hot-dip galvanized layer, the ratio (B / A (%)) of the area fraction B of the [Zn phase] of the coating structure to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] in at least one of the cross sections is 20% or more, [Group A] Si: 0.0001 to 2 mass% [Group B] Any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C: 0.0001 to 2 mass % in total.
3. The Zn-Al-Mg hot-dip coated steel sheet according to claim 1 or 2, characterized in that: The area fraction of the [Zn phase] in at least one of the cross sections is 10% or more.
4. The Zn-Al-Mg hot-dip coated steel sheet according to claim 1 or 2, characterized in that: The average grain size of the [Zn phase] in the plating structure in at least one of the cross sections is 2.5 to 10 μm.
5. The Zn-Al-Mg hot-dip coated steel sheet according to claim 3, characterized in that: The average grain size of the [Zn phase] in the plating structure in at least one of the cross sections is 2.5 to 10 μm.
6. The Zn-Al-Mg hot-dip plated steel sheet according to claim 2, wherein: The hot-dip coating layer has an average composition containing the group A in mass %.
7. The Zn-Al-Mg hot-dip plated steel sheet according to claim 2, wherein: The hot-dip coating layer has an average composition containing the B group in mass %.
Citation Information
Patent Citations
Hot dip zinc-aluminum-magnesium plated steel sheet good in corrosion resistance and surface appearance and its production
JP1998226865A
Hot dip zn-al-mg coated steel sheet excellent in corrosion resistance and external surface appearance, and its production
JP1998306357A
Hot-dip zn-al-mg plated steel sheet superior in workability and corrosion resistance, and manufacturing method therefor
JP2004068075A
Polyimide precursor composition
JP2022094356A